Variability and character association in cinnamon germplasm (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at the Regional Spices Research Center, BARI during May 2014 to April 2015 to study the variability and character association in cinnamon germplasm taking the characters - tree growth, leaf characteristics, bark thickness, specific bark weight and quality of bark of cinnamon plants. Range, variance and coefficient of variation of 30 different characters showed variations in 53 cinnamon accessions. High coefficient of variation was found for base girth, main stem height, number of tertiary branches/plant, tree volume, fresh and dry bark weight of tertiary branches. Bark thickness and specific bark weight gradually declined from main stem to lateral branches. The hierarchical cluster analysis with single scaled dendrogram showed eight clusters due to variation among the germplasm. Cluster III contained maximum 14 genotypes followed by cluster I and cluster VII, each having 12 genotypes. Association analysis revealed that significant correlation of base girth with tree volume, and secondary branches/plant had also significant correlation with leaf thickness and tree volume. It also revealed that significant correlation of fresh bark thickness of main stem with fresh bark thickness of primary, secondary and tertiary stems, also with fresh and dry bark weight of main, primary, secondary and tertiary stems. Specific bark weight had also significant correlation with fresh and dry bark weight of main, primary, secondary and tertiary barks.Bangladesh J. Agril. Res. 41(3): 555-564, September 2016